Planned home birth: benefits, risks, and opportunities - Zielinski R; Ackerson K; Kane Low L (Dove Medical Press, 2015)
Ruth Zielinski,1 Kelly Ackerson,2 Lisa Kane Low1,3,4 1School of Nursing, University of Michigan, Ann Arbor, MI, USA; 2Bronson School of Nursing, Western Michigan University, Kalamazoo, MI, USA; 3Department of Obstetrics and Gynecology, Medical School, University of Michigan, Ann Arbor, MI, USA; 4Women’s Studies Department, University of Michigan, Ann Arbor, MI, USA Abstract: While the number of women in developed countries who plan a home birth is low, the number has increased over the past decade in the US, and there is evidence that more women would choose this option if it were readily available. Rates of planned home birth range from 0.1% in Sweden to 20% in the Netherlands, where home birth has always been an integrated part of the maternity system. Benefits of planned home birth include lower rates of maternal morbidity, such as postpartum hemorrhage, and perineal lacerations, and lower rates of interventions such as episiotomy, instrumental vaginal birth, and cesarean birth. Women who have a planned home birth have high rates of satisfaction related to home being a more comfortable environment and feeling more in control of the experience. While maternal outcomes related to planned birth at home have been consistently positive within the literature, reported neonatal outcomes during planned home birth are more variable. While the majority of investigations of planned home birth compared with hospital birth have found no difference in intrapartum fetal deaths, neonatal deaths, low Apgar scores, or admission to the neonatal intensive care unit, there have been reports in the US, as well as a meta-analysis, that indicated more adverse neonatal outcomes associated with home birth. There are multiple challenges associated with research designs focused on planned home birth, in part because conducting randomized controlled trials is not feasible. This report will review current research studies published between 2004 and 2014 related to maternal and neonatal outcomes of planned home birth, and discuss strengths, limitations, and opportunities regarding planned home birth. Keywords: home birth, hospital birth, risks, benefits, maternal satisfaction